Implementation, effectiveness and experience with remote laboratory in engineering education - Rojko, Andreja (Organizacija (Kranj), 2009)
Modern educational methods bring many new challenges from the pedagogical, as well as from the technical aspect. One of the more significant is the integration of information and communication technology into the educational process. These is particularly noticeable in the engineering education where the requests of the industry for a faster and more efficient acquisition of knowledge and practical skills lead to a constant search for new solutions in the learning process which would attract and motivate students, as well as be user friendly. This is especially difficult to be reached with the practical education which is usually composed of laboratory exercises that are bound to a specific time and place. One of the possible solutions are the remote laboratories which offer the possibility of the implementation of real remote laboratory experiments in the educational institutionsć laboratories and, therefore, enhance the studentsć knowledge and capability for dealing with some technical problems without the need for their physical presence in the laboratory. In the article, the example of a successful implementation of the remote laboratory in the field of engineering, developed and operating in the Moodle environment, is presented. The laboratory does not only represent the framework for the experiment implementation, but it also offers courses with complete documentation, therefore courses can be performed on distance. As an example, the case of the most widely used course from remote laboratory is presented, i.e., the ĆControl of nonlinear mechanismĆ course. Special attention is given to the description of the booking process for remote experiments, the execution of remote experiments and the applied user interface. The evaluation of the interface usability from the point of view of end users was performed via the acknowledged SUMI method. Additionally, another questionnaire was prepared in order to investigate the studentsć opinion about working in the remote laboratory. The results have shown that the presented remote laboratory is user friendly and accepted by both teachers and students as a suitable and interesting supplement to the conventional laboratory exercises.
Keywords: laboratoriji; mehatronika; tehnika; visoko šolstvo; izobraževanje na daljavo; elektronsko izobraževanje